(untitled) (Academicia Globe: Inderscience Research, 2023)
The issues of communicative teaching of a foreign language in the system of vocational education have acquired special importance in the context of the increasing importance of foreign languages caused by the trends of globalization and internationalization in recent decades. Orientation to new educational goals requires changes in methods and forms of organization of the educational process. A teacher of a foreign language should be proficient in modern teaching technology, using interactive technologies, which are especially appropriate for accelerated teaching of a foreign language to students. The combination of traditional intensive teaching methods and modern interactive methods is an important condition for effective teaching of a foreign language at a university.